The Effect of Exercise Intensity and Volume on Metabolic Phenotype in Patients with Metabolic Syndrome: A Randomized Controlled Trial - Von Korn, Pia; Keating, Shelley; Mueller, Stephan; Haller, Bernhard; Kraenkel, Nicolle; Dinges, Sophia; Duvinage, Andre; Scherr, Johannes; Wisloff, Ulrik; Tjonna, Arnt Erik; Halle, Martin; Lechner, Katharina (Metabolic Syndrome and Related Disorders, 2021)
Background: Moderate intensity continuous training (MICT) ameliorates dysmetabolism in patients with metabolic syndrome (MetS). The impact of low-(1HIIT) versus high-volume high-intensity interval training (4HIIT) versus MICT on central adiposity, insulin resistance, and atherogenic dyslipidemia in patients with MetS has not yet been reported. Methods: Twenty-nine patients with MetS according to International Diabetes Federation criteria (nine females, age 61 ± 5 years, body mass index 31.1 ± 3.7 kg/m2, waist circumference (WC) 102.2 ± 10.6 cm, 108.5 ± 8.6 cm) were randomized (1:1:1) to 16 weeks of (1) MICT (5 × 30 min/week, 35%-50% heart rate reserve (HRR), (2) 1HIIT (3 × 17 min/week incl. 4 min @80%-90% HRR), and (3) 4HIIT (3 × 38 min/week incl. 4 × 4 min @80%-90% HRR). Peak oxygen uptake (V˙O2peak), WC and anthropometric/metabolic indices indicative of MetS, fasting glucose/insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), dyslipidemia, and respiratory exchange ratio (RER) at warm-up were quantified at baseline and study completion. Analysis of variance and paired t tests were used for statistical analysis. Analyses were performed after checking for parametric distribution. Results: There were no significant differences between groups in waist-To-height ratio (: Δ-0.10 ±-0.05, Δ-0.08 ±-0.06, P = 0.916), WC (: Δ-1.4 ±-0.1 cm, Δ0.1 ± 0.9 cm, P = 0.590), fasting glucose (Δ-1.18 ± 16.7 μU/mL, P = 0.773), fasting insulin (Δ0.76 ± 13.4 μU/mL, P = 0.509), HOMA-IR (Δ0.55 ± 4.1, P = 0.158), atherogenic dyslipidemia [triglycerides (TAG) Δ-10.1 ± 46.9 mg/dL, P = 0.468, high-density lipoprotein cholesterol (HDL-C) Δ1.5 ± 5.4, P = 0.665, TAG/HDL-C-0.19 ± 1.3, P = 0.502], V˙O2peak (P = 0.999), or RER (P = 0.842). In the entire group, waist-To-height-ratio and V˙O2peak significantly improved by a clinically meaningful amount (Δ2.7 ± 0.9 mL/min/kg; P < 0.001) and RER at warm-up significantly decreased (Δ-0.03 ± 0.06, P = 0.039). Conclusion: In patients with MetS, there was no significant difference between HIIT, irrespective of volume, to MICT for improving exercise capacity or metabolic health.
CRIS-Team Scopus Importer:2023-03-08
Keywords: atherogenic dyslipidemia; exercise training; free fatty acid oxidation; high intensity interval training; metabolic syndrome; visceral adiposity